Evaluation Basic Online Training Program for Character-Building of Transportation Cadets at Indonesian Aviation School Banyuwangi - Rangga Handhika Putra; Arief Rusdyansyah; Agung Wahyu Wicaksono; Untung Lestari Nur Wibowo; Ikhwanul Qiram (Ilomata International Journal of Management, 2023)
The base period of character formation activities for transportation cadets is called "MADATUKAR" a mandatory program for new cadets (juniors) who will enter educational institutions within the Human Resource Development Agency of Ministry of Transportation Republic of Indonesia. This study aims to understand the effectiveness of MADATUKAR program at the Banyuwangi Indonesian Aviation School (APIB). This type of research uses a qualitative descriptive method. Data analysis includes the stages of reduction, presentation, and verification. The results show that character building through the MADATUKAR program is most important for cadets. Characters formed are religious, responsible, disciplined, social care, hard work, independence, curiosity, national spirit, love of the motherland, care for the environment, communication, and respect for achievement. Character building through 3 stages; planning, implementation, and evaluation. Meanwhile, the method used is the method of internalization, habituation, exemplary, and discipline coaching. In the process, the character formation of cadets is influenced by internal factors (instinct and will) and external factors (education and environment).